Analisis “ Prinsip Kesukarelaan” Dalam Penerapan Corporate Social Regulation (CSR) Ditinjau Dari Undang-Undang Perseroan Terbatas - Karima Daniswari; Sumriyah Sumriyah (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
This research analyzes the principle of volunteerism in the context of implementing Corporate Social Responsibility (CSR) by companies that are subject to the Limited Liability Company Law. The main objective of the research is to explore the concept of the Voluntary Principle and understand its relevance in the context of corporate social responsibility, with special emphasis on Article 74 of the Limited Liability Company Law as the legal basis for CSR. This research uses normative juridical legal research methods with a statutory regulatory approach. Research findings show that the implementation of CSR in Indonesia, as mandated by Article 74 of Law Number 40 of 2007, creates a contradiction between legal obligations and the Voluntary Principles contained in CSR which was originally interpreted as voluntary corporate charity. However, as time goes by, where companies primarily operating in the Natural Resources sector have contributed to serious damage to the environment, now the Voluntary Principle can be interpreted as company compliance with regulations while making voluntary efforts to exceed existing legal limits. Conclusion of the research illustrates that good integration between Voluntary Principles and legal obligations can create a solid foundation for CSR implementation. Even though CSR obligations are mandatory, companies still have the freedom to determine programs and budgets according to their respective volunteers and abilities. A holistic and sustainable CSR strategy can have a greater positive impact than simply complying with regulations.